A Low-Cost Tensionable Quadriceps Tendon Rupture Repair Using Transosseous Tunnels - João Lopes; Gonçalo Martinho, M.D.; Manuel Oliveira, M.D.; André Guimarães, M.D.; Carlos Queirós, M.D.; João Raposo, M.D.; Levi Reina Fernandes, M.D. (Arthroscopy Techniques)
A quadriceps tendon rupture is a traumatic injury of the quadriceps insertion on the patella leading to a disruption in the knee extensor mechanism. Diagnosis is usually made clinically with a palpable defect proximal to the superior pole of the patella coupled with the patient’s inability to perform a straight leg raise and confirmed on radiographs, ultrasonography, or magnetic resonance imaging scan. When the extensor mechanism is disrupted, operative repair is indicated. Two common techniques have been described for repair: the transosseous) repair and the suture anchor repair, and both have shown good clinical results. Nevertheless, gap formation is always a concern, and there is no consensus if one technique is superior to the other in this matter. We propose a low-cost, tensionable, transosseous anatomic repair that results in a tight construction.